Sistem Informasi Perpustakaan Prodi Teknik Informatika Universitas Malikussaleh - Sujacka Retno, Rozzi Kesuma Dinata, Zeny Arsya Fortilla (LPPM-UNIKI, 2023)
There are various problems in the Informatics Engineering library at Universitas Malikussaleh, one of which is book management, where this data is very necessary for the book data collection process. Considering the problems faced by staff in the library section, an idea was formulated to create a data processing system based on an information system. Fast, high-quality and smooth data processing is needed by all types of organizations to assist in achieving work goals or objectives, especially in the library section. This research aims to overcome this problem by creating a system that aims to optimize the performance of staff in the Informatics Engineering library at Universitas Malikussaleh. The system is built on a desktop basis.